Clinical characteristics of patients with GFAP-IgG coexisting with AQP4-IgG or MOG-IgG - Li, Qingchen; Chen, Xinyun (Frontiers in Immunology, 2025)
BackgroundGlial fibrillary acidic protein–immunoglobulin G (GFAP-IgG) can coexist with aquaporin-4–IgG (AQP4-IgG) or myelin oligodendrocyte glycoprotein–IgG (MOG-IgG). We aimed to investigate the clinical characteristics of patients with GFAP-IgG coexisting with AQP4-IgG or MOG-IgG.MethodsWe retrospectively collected data from 81 GFAP-IgG-positive patients and described and compared the clinical characteristics of those with GFAP-IgG coexisting with AQP4-IgG or MOG-IgG.Results(1) Among the 81 GFAP-IgG-positive patients, nine (11.1%) were positive for AQP4-IgG and seven (8.6%) were positive for MOG-IgG. The clinical manifestations of overlapping syndromes were diverse; all patients met the clinical phenotype of autoimmune GFAP astrocytopathy (A-GFAP-A) and also fulfilled the diagnostic criteria for neuromyelitis optica spectrum disorders or MOG antibody-associated disorders. Compared with the GFAP-AQP4 overlapping syndrome, the GFAP-MOG overlapping syndrome had a higher frequency of seizures (57.1% vs. 0, p = 0.019). (2) Compared with the nonoverlapping syndrome group, the overlapping syndrome group had more women (68.6% vs. 32.3%, p = 0.008), a higher incidence of optic neuritis (ON) (43.8% vs. 4.6%, p < 0.001), lower CSF white blood cell counts (median: 30 cells/mm3 vs. 94 cells/mm3, p = 0.001) and protein levels (median: 0.375 g/L vs. 0.78 g/L, p < 0.001), and a higher proportion of patients receiving long-term immunotherapy (68.8% vs.13.8%, p < 0.001).ConclusionsAmong patients with A-GFAP-A, 20% had concurrent AQP4-IgG or MOG-IgG, exhibiting distinct clinical features that suggest a different disease phenotype driven by overlapping autoimmune mechanisms.